Dominant Biological Control Over Upwelling on pCO2 in Sea East of Sri Lanka. Issue 10 (11th October 2018) - Chakraborty, Kunal; Valsala, Vinu; Gupta, G.V.M.; Sarma, V.V.S.S.
Abstract: Upwelling enhances pCO2 levels due to injection of carbon‐rich water to the surface despite the removal of carbon due to increase in primary production supported by enhanced nutrients. It is hypothesized that in the Bay of Bengal, upwelling may decrease pCO2 due to existence of low saline and pCO2 ‐poor waters in the subsurface layer. In order to test this hypothesis, a high‐resolution state‐of‐the‐art ocean biogeochemical model (Regional Ocean Modeling System) runs are examined at the sea east of Sri Lanka (SESL) where intense upwelling occurs during summer monsoon (May to August). Upwelling enhances pCO2 by 34 μatm, whereas decrease in surface temperature and increase in surface salinity reduce pCO2 by 24 μatm. The estimated net effect of upwelling is an increase in pCO2 by 10 μatm. In contrast, soft and hard tissues together contribute to a decrease in pCO2 by 21 μatm suggesting that the biological effect dominates over upwelling, resulting in a net decrease of pCO2 by 11 μatm in the SESL. This striking contrast between the increase in pCO2 due to physical dynamics (upwelling) and the removal of pCO2 due to biological processes is caused by shallow (deep) nitracline (dissolved inorganic carbon‐isoline) in the SESL. Key Points: Phytoplankton bloom, in response to upwelling, decreases pCO2 in sea east of Sri Lanka (SESL) during summer monsoon Relatively shallow nitracline and deep DIC‐cline is observed in the SESL Removal of pCO2 due to biological production dominates increase of pCO2 due to upwelling in SESL